(untitled) (Research, Society and Development, 2022)
The implementation of Information Systems (IS) in public agencies has been growing, motivated mainly by the need to modernize and improve the services and procedures provided, the management, and performance of institutions, in addition to increasing the connection with citizens. In this context, Sigen+, Cidasc’s SI, has been implemented and used for the control of poultry slaughter since 2018, but it has never been diagnosed and analyzed. Therefore, this study carried out a diagnosis in Sigen+ with the objective of identifying its positive and negative characteristics and functionalities, based on users’ perception. Data were collected through the application of a questionnaire with open and closed questions, analyzed by SWOT associated with frequency analysis, Fleiss Kappa test and agreement rate. Of the 24 professionals invited to participate in the research, 17 responded to the questionnaire. The results demonstrate that there are a greater number of strengths and positive features, with emphasis on search filters, usability, and reporting with clear and complete information. There are points that need improvement, such as the absence of attributes for better injury classification and require immediate attention to reduce the risk of system failure. The analyzed screens of the system fully satisfy users in terms of information and data quality. Sigen+ proved to be a quality IS, with characteristics that determine the perception of value and satisfaction of users and with data quality.